The State of Morelos: Towards a Knowledge Society? Considerations Based on the Development of Science, Higher Education and ICT - Serafín Ángel Torres Velandia; Manuel Francisco Aguilar Tamayo; Silvana Girardo; María Magdalena Villalobos Hernández (Universidad Autónoma de Baja California, 2012)
This paper provides an overview of some of the gains and constraints in the process of construction of a knowledge society in the state of Morelos, Mexico, focusing mainly on the development and use of ICT and on the role of institutions of higher education (IES- acronym in Spanish). To this end, documentary and field research methods were applied; interviews were conducted with experts and a case study from the Universidad Autónoma del Estado de Morelos [Autonomous University of the State of Morelos] is reported. The following conclusions were highlighted: a) while Morelos has made significant progress in scientific and technological matters, challenges remain in order to be able to even speak of a knowledge society; b) the fact that institutions of higher education have ICT does not necessarily mean that they have adequately appropriated them and employ them to improve their processes; and c) institutions of higher education need to generate outreach programs that engage with the region so that technological developments are translated into benefits for the people of Morelos.